Mengeksplorasi kesadaran merek terhadap minat beli ulang melalui sikap terhadap merek - Hanfan, Ahmad (Performance, 2017)
Purpose: The purpose of this study is to analyze the influence of brand awareness on brand attitude, brand image on brand attitude, brand personality on brand attitude, and brand attitude on repurchase intention. Research problem: This research problem is sourced from the existence of research gap of influence of brand awareness on repurchase intention and business phenomenon that happened at brand value of instant noodle of Indomie brand that experienced fluctuation. Findings: The results show that brand awareness influences brand attitude, brand image influences brand attitude, brand personality influences brand attitude, and brand attitude influences repurchase intention. Implications: Based on analysis of full model, obtained the theoretical implication that is when the companies increase repurchase intention, companies need to consider how to improve brand attitude. Brand attitude is influenced by brand awareness, brand image, and brand personality. While, managerial implication in this research is that brand attitude has positive and significant effect on repurchase intention. In increasing repurchase intention, brand awareness plays an important role in improving brand attitude in order to encourage repurchase intention, followed by brand image and brand personality. Originality: The originality of this research is that the relationship between brand awareness and repurchase intention is still a debate among researchers. Therefore, this study attempts to explain the relationship between brand awareness and repurchase intention by adding mediation variable, namely brand attitude that is influenced by brand image and brand personality. Keywords: brand awareness, brand image, brand personality, attitudes toward brands, repurchase intention.